LEADERSHIP MANAGEMENT IN IMPROVING THE QUALITY OF SERVICES IN PRIVATE UNIVERSITY (STUDY AT STAI AL-MA'ARIF, ASHANTA, AL-AZHAR JAMBI PROVINCE) - Hindun Hindun; Norainun Norainun; Yusraini Yusraini; Ely Surayya (Dinasti International Journal of Education Management And Social Science, 2021)
Leadership Management in Improving Service Quality in private universities in Jambi Province which is the target of research is under the Regional Kopertais Environment of UIN Sulthan Thaha Saifuddin Jambi. The quality of service in an organization is the main focus, considering that services that can be carried out effectively and efficiently are a dream for all customers, and the goal of the organization itself. In this study, the researcher used a qualitative-naturalistic approach. Through this qualitative approach, it is hoped that an overview of leadership management and service improvement will be raised. The naturalistic approach demands data collection in a natural setting. The method used in collecting data in the field is the method of observation, interviews and documentation. The results of this study indicate that the implementation of service quality carried out by the Three Private STAIs in the Kopertais Region XIII Jambi City environment have both implemented the eight standards as specified in the planning. However, there is a very significant difference between Ashanta and Al-Azhar Private STAI and Al-Marif Private STAI. Of the three STAIs, the one that is superior is the Al-Ma'rif Private STAI, with evidence that can be seen from the number of students quite a lot, and the majority of the teaching staff are S2 qualified and some are even S3 qualified. When viewed from the satisfaction of service quality from customers, Al-Ma'rif Private STAI has the advantages of the three Private STAIs that are the targets of researchers, satisfaction indicators such as learning facilities and infrastructure are independent and have their own. In addition, the management of financing is more organized and transparent from the Foundation and the Chairperson of the Foundation to their subordinates. Payment of honorarium for staff and lecturers in accordance with the provisions specified and paid on time.